Informal Recyclers' Health Inequities in Vancouver, BC. (August 2018) - Wittmer, Josie; Parizeau, Kate
We explore informal recyclers' perceptions and experiences of the social determinants of health in Vancouver, Canada, and investigate the factors that contribute to the environmental health inequities they experience. Based on in-depth interviews with 40 informal recyclers and 7 key informants, we used a social determinants of health framework to detail the health threats that informal recyclers associated with their work and the factors that influenced their access to health-related resources and services. Our analysis reveals that the structural factors influencing environmental health inequities included insufficient government resources for low-income urbanites; the potential for stigma, clientization, and discrimination at some health and social service providers; and the legal marginalization of informal recycling and associated activities. We conclude that Vancouver's informal recyclers experience inequitable access to health-related resources and services, and they are knowledgeable observers of the factors that influence their own health and well-being.